Assessment of brain compliance in patients with migraine: use of non-invasive intracranial monitoring in outpatient clinics - Bem Junior, Luiz Severo; Ferreira Neto, Otávio da Cunha; Pereira, Igor Antônio; Valença, Marcelo Moraes; Azevedo Filho, Hildo Rocha Cirne de (Frontiers in Neurology, 2025)
This study aimed to characterize the morphology of the cerebral compliance monitoring curve in patients with primary headaches, specifically differentiating between migraine with aura and migraine without aura, using non-invasive intracranial monitoring. This study is innovative in that it applies Brain4Care® technology in an outpatient setting to differentiate migraine types, making a significant contribution to understanding the pathophysiology of headaches and thus improving clinical management strategies. A cross-sectional, prospective study was carried out with 50 patients seen at an outpatient clinic specializing in pain. Variables such as the P2/P1 ratio, time to peak (TTP), and the morphology of the cerebral compliance wave were assessed, as well as demographic and clinical factors. A high prevalence of altered P2/P1 ratio (P2 > P1) was observed in patients suffering from migraine with aura. Statistical analyses indicated significant associations between this ratio and factors such as age and the presence of symptoms at the time of the examination. The findings emphasize the importance of the P2/P1 ratio and TTP as indicators for differentiating primary headaches. A non-invasive intracranial monitoring offers valuable insights into brain dynamics, enabling more accurate diagnoses and personalized interventions in outpatient settings. Brain4Care® technology is emerging as a promising tool for the non-invasive monitoring of cerebral compliance, with the potential to revolutionize clinical management of migraines. Future studies should extend the validation of these findings and explore new applications for this technology in clinical practices.